(untitled) (INNOVATIVE ECONOMY, 2020)
Boiko O. ANALYSIS OF TECHNOLOGICAL INNOVATIONS IN A CRYPTOCURRENCY INTERNATIONAL PAYMENT SYSTEM Purpose. The aim of the article is to reveal technological characteristics of the Blockchain for more adequate assessment of payment systems, which are based on this technology, from the technical and economic point of view. Methodology of research. The study uses the analogy method and makes a detailed description of the relevant technologies. Findings. This paper collects and describes different techniques and technologies that solve technical problems in the Blockchain-based international payment system in cryptocurrency. The DSA digital signatures mechanism is considered, a suitable structure for the digital data storage is proposed and the transaction validation process is described. A double-entry accounting method as well as other technologies for describing the Blockchain technology is used. Furthermore, a payment and emission cryptocurrency transactions are simulated in terms of the above-mentioned technologies. The importance of the research subject is confirmed by the previous research, which is based on factual material showing the expansion of the cryptocurrencies in the system of international settlements and transformation of the forms and fundamental principles of international trade. Actuality of the research topic is derived from the factual material testifying to both expansion of international payments in cryptocurrency and transformation of forms and fundamental principles of international trade. Originality. Payment and emission transactions in the cryptographic system are simulated. A digital data storage structure is scrutinized and a transaction validation process considered. Practical value. The results confirm the novelty of decentralized currencies and can be used both in theoretical and practical domains for modelling of numerous Blockchain based services. Further research should stem from the prospects of decentralized payment systems. A similar analysis may apply to another group of decentralized payment systems that serve as platforms for numerous payment services. Such topics as opportunities and threats caused by the usage of cryptomoney, institutional framework, co-existence of fiat and cryptographic payment systems, different levels of economic security and volatility represent scientific interest and may be subject to future studies. Key words: cryptographic currency, currency innovation, decentralized payment system, Blockchain, international payments, financial globalization.